ALETHEIA: KATALISATOR PUBLIKASI ILMIAH BERBASIS OPEN JOURNAL SYSTEM (OJS) - Saksono, Herie; Utami, Karina Juniarti (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
The turbulence of technological advancements in the digital era has transformed various aspects of life, including scientific publications, which have become a determining factor in decision-making processes. Although the global trend towards open access presents significant opportunities for academics, there remains a gap between potential and realization in the field, particularly among students and faculty. This Community Service Program (PKM) aims to provide a credible scientific publication platform, enhance the quality and quantity of publications, facilitate the fulfillment of the Tri Dharma of Higher Education, expand the visibility of research outputs, and hone students' skills in writing and publishing scientific works. The implemented method encompasses the development of a journal using the Open Journal System (OJS), capacity building of human resources in scientific writing, and strengthening of content, impact, and sustainability. The result of this PKM is the establishment of